"The value of the soul." The discourses of management as modes of subjectivity at work. - Cecilia Beatriz Soria (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
This review describes the main guidelines, questions and hypotheses that traverse the recent work of Marcela B. Zangaro, called "Subjectivity and work. A Foucauldian reading of management", edited by Herramienta. The book, as its title indicates, dives for two fundamental topics of modernity: the modes of subjectification and labor issues. The author, from a critical perspective, links the input matrix from the Foucauldian and other aspects of the New Sociology of Capitalism and Critical Discourse Analysis. Since this articulation, she analyzes a broad set of discourses of management, understanding them as a technology of power, a technology of self, which organizes the bodies and emotions of the workers. In this sense, the text becomes a valuable input to understand the practices of subjectivity in the context of the many changes that have experienced the world of work in recent decades. These mutations can only be examined in the light of the new forms of organization and capital accumulation, complainant labor force, in its broadest sense, such as physical and mental abilities present in the body and embodiment of the workers.